The Effectiveness of an Anesthetic Protocol for Enhancing Recovery After Laparoscopic Cholecystectomy - Nateanong, Srisungwan; Angkurawaranon, Chotirot; Jitmala, Nunmanas (Nursing Journal CMU, 2023)
This implementation research aimed to develop and implement an anesthetic protocol for enhancing recovery after laparoscopic cholecystectomy in a tertiary hospital. Participants included 30 anesthetists and 105 patients. All patients underwent surgery: 50 patients without the anesthetic protocol, from September to December 2020, and 55 patients with the protocol, from February to May 2021. The research process was divided into 2 phases, including development and action, based on the framework of the Center for Advanced Nursing Practice Evidence-based Practice model proposed by Soukup. The research instruments included the anesthetic protocol for enhancing recovery after laparoscopic cholecystectomy, the satisfaction with the anesthetics, and the postoperative recovery results. Data were analyzed using descriptive statistics, frequency, percentage, mean standard deviation, independent t-test, and chi-square test. The results showed that: the developed practice guidelines for enhancing recovery after laparoscopic cholecystectomy was composed of 3 phases: 1) preoperative phase; 2) intraoperative phase; and 3) postoperative phase. Results of the guideline implementation showed that there were statistically significant differences in the quality of postoperative recovery, in postoperative pain at 6 hours, physical activity (p < .05) and the time available for discharge (p < 0.001). There were no differences in the quality of 0-2-hour postoperative pain, meal start, or postoperative complications. Finally, the protocol gained the highest level of satisfaction for use from anesthetist participants. The anesthetic protocol for enhancing recovery after laparoscopic cholecystectomy can be used effectively in terms of relieving pain at 6 hours post-operation, promoting an ambulation result in decreasing the risk of postoperative complications.